Enzyme hydrolysis of old newspaper to produce simple sugar for fermentation process - Noor Fauzani, Ayop (2013)
Production of fermentable sugar from lignocellulosic material was attempted by many researchers. Nowadays, this is because of plenty lignocellulosic biomass waste available around the world including Malaysia. Newspaper is a type of lignocellulosic sources because newspaper was made from softwood that contains cellulose, hemicelluloses and lignin. Cellulose component in newspaper is the major component with 45-50 %. The celluloses were able to be converted into simple sugar, which is glucose. Enzymatic hydrolysis is preferred for the conversion because less cost and high conversion. In this study, cellulase enzyme from Novozyme was used to hydrolyze newspaper for glucose production. By applying one-factor-at-time (OFAT), six parameters were being studied. They are surfactant ratio, enzyme loading, buffer pH, incubation temperature, agitation speed and incubation time. In all experiments, glucose production was monitored by DNS method. The result obtained show that at surfactant ratio 0.2:0.8 of TX-21: TWEEN-80, 1.0 ml of cellulase enzyme, at pH 6.0 when mixed with 0.2 g substrate at 50 oC and agitated at 200 rpm for 96 h is suitable for enzyme reaction. Those optimum parameters obtained gave the higher glucose production at 0.73 0.02 g/L.